Complete remission after sintilimab combined with chemoradiotherapy in double primary head and neck carcinoma: case report - Lu, Xiameng; Tan, Bibo; Yang, Liuting; Huang, Suning (Frontiers in Oncology, 2024)
The simultaneous occurrence of head and neck squamous carcinoma in two anatomical sites is rare, posing challenges in treatment selection. This paper presents a clinical case of concurrent hypopharyngeal carcinoma and nasopharyngeal carcinoma, successfully treated with a combination of chemoradiotherapy and an immune checkpoint inhibitor. The patient achieved complete remission and progression-free survival of nearly 3 years, with preserved organ function and minimal toxic side effects, leading to a good quality of life. This case highlights the potential of combined concurrent chemoradiotherapy and immune checkpoint inhibitors in managing double primary HNSCC, offering a promising treatment option for these patients.